Adsorption-Photocatalytic Degradation Of Chicken Processing Wastewater Using Powdered Activated Carbon-Supported Graphitic Carbon Nitride - Leong, Ken Lap (2020)
Due to the expansion of agricultural sector, a massive volume of chicken processing wastewater has been produced and the conventional technologies are ineffective to remove organic and inorganic compounds. Thus, this project will solely investigate the performance for the adsorption-photocatalytic degradation of chicken processing wastewater using powdered activated carbon (PAC) supported graphitic carbon nitride (g-C3N4). Different weight percentage of g-C3N4 (20 wt%, 40 wt% and 60 wt%) were successfully supported onto the AC surface. 20 wt% g-C3N4/PAC composite, 40 wt% gC3N4/PAC composite and 60 wt% g-C3N4/PAC composite were prepared. The synthesized catalysts were characterized using Brunauer-Emmett-Teller (BET), Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and Electron Dispersive X-ray (EDX). Through BET analysis, the specific surface area of 20 wt% g-C3N4/PAC composite, 40 wt% g-C3N4/PAC composite and 60 wt% g-C3N4/PAC composite were larger than that of pure g-C3N4 and this was attributed to the presence of AC that provided a larger surface area. The nitrogen element was identified in gC3N4/PAC composites by EDX and the FTIR spectra show that the gC3N4/PAC composites had the characteristic functional group of g-C3N4 which are aromatic C-N and C=N bonds. It was noticeable that the incorporation of AC did not improve the performance in orthophosphate and ammonia nitrogen removal in the dark adsorption. Overall, AC achieved the highest COD removal efficiency (79.00 %) in the dark adsorption. Meanwhile, the pure gC3N4 achieved the highest orthophosphate (49.10 %) and ammonia nitrogen removal efficiency (100 %) in the dark adsorption. 20 wt% g-C3N4/PAC composite showed the highest COD removal efficiency (47.00 %) by photodegradation under the irradiation of LED light. The pure g-C3N4 showed the highest orthophosphate (49.00 %) removal efficiency by photodegradation under the irradiation of LED light; whereas, the 60 wt% g-C3N4/PAC composite showed the highest ammonia nitrogen removal efficiency (52.90 %) by photodegradation under the irradiation of LED light.